Mulheres negras nos carnavais paulistanos: quem são elas? (1921-1967) - Silva, Zélia Lopes Da (Centro de Filosofia e Ciências Humanas e Centro de Comunicação e Expressão da Universidade Federal de Santa Catarina, 2018)
Abstract: The analysis regarding the participation of black women in carnival celebrations falls within well beyond the group's interests, considering that these festivities’ paradigms and gender and women's issues cross the subject, inscribing the agenda in transnational reflections involving protagonists of different spectra. In this text, the main intention is to articulate these fields, without losing sight of the specifics related to Afro-descendant revellers and their mishaps, which manifest themselves immediately in the limitations of memorial records and historiography that transversally explore their role in these Sao Paulo unmistakable carnival frolics. In this sense, it is possible to see a sexist and selective reading of records of these appearances and, at the same time, it has a fragmented memory of this appearance that little has changed over the years. This route will be monitored between years 1921, the start date of black women appearance in a carnival cord, and 1967, the closing date of São Paulo unofficial” carnivals. Therefore, who are the black women who were identified and worthy of this protagonism?

Resumo: A análise referente a participação das mulheres negras nas pândegas carnavalescas insere-se muito além dos interesses de grupo, considerando que os paradigmas sobre essas festividades e as questões de gênero e do feminino atravessam o assunto, inscrevendo o temário em reflexões transnacionais que envolvem protagonistas de espectros distintos. Neste texto, a intenção é articular esses campos, sem perder de vista as especificidades referentes às folionas afrodescendentes e seus percalços, que se manifestam, de imediato, nas limitações dos registros memoriais e da historiografia que transversalmente exploram o seu papel nesses folguedos carnavalescos manifestos na cidade de São Paulo. Nesse sentido, percebe-se uma leitura sexista e seletiva dos registros dessas participações e, ao mesmo tempo, tem-se uma memória fragmentária dessa participação que pouco foi alterada ao longo dos anos. Esse percurso será acompanhado entre os anos de 1921, data inicial da aparição de mulheres negras em um “cordão carnavalesco”, ao ano de 1967, data do encerramento dos carnavais “não oficiais” em São Paulo. Quem são, portanto, as mulheres negras que foram identificadas e dignas desse protagonismo?
Black Women in São Paulo Carnivals: Who Are They? (1921-1967)
Keywords: Brazil; Afro-descendant Women; Brazilian Carnival; Gender; São Paulo Carnival; Brasil; Mulheres afrodescendentes; Carnaval brasileiro; Gênero; Carnaval paulistano